Effect of Biltong Dried Beef Processing on the Reduction of Listeria monocytogenes, E. coli O157:H7, and Staphylococcus aureus, and the Contribution of the Major Marinade Components - Kavya Gavai; Caitlin Karolenko; Peter M. Muriana (Microorganisms, 2022)
Biltong is a dry beef product that is manufactured without a heat lethality step, raising concerns of whether effective microbial pathogen reduction can occur during biltong processing. Raw beef inoculated with 4-strain cocktails of either E. coli O157:H7, Listeria monocytogenes, or Staphylococcus aureus, and processed with a standard biltong process, were shown to incur a >5-log reduction in 6–8 days after marination by vacuum-tumbling for 30 min in vinegar, salt, spices (coriander, pepper) when dried at 23.9 °C (75 °F) at 55% relative humidity (RH). Pathogenic challenge strains were acid-adapted in media containing 1% glucose to ensure that the process was sufficiently robust to inhibit acid tolerant strains. Internal water activity (Aw) reached < 0.85 at 5-log reduction levels, ensuring that conditions were lower than that which would support bacterial growth, or toxin production by S. aureus should it be internalized during vacuum tumbling. This was further confirmed by ELISA testing for staphylococcal enterotoxins A and B (SEA, SEB) after marination and again after 10 days of drying whereby levels were lower than initial post-marination levels. Comparison of log reduction curves obtained for E. coli O157:H7, L. monocytogenes, S. aureus, and Salmonella (prior study) showed that microbial reduction was not significantly different (p < 0.05) demonstrating that even without a heat lethality step, the biltong process we examined produces a safe beef product according to USDA-FSIS guidelines.